Virtual testing wind and analysis performance of UMP lab circuit - Mohd Faez, Baharom (2009)
The purpose of this project is to study about the virtual testing wind and analysis performance of the UMP lab circuit. But the main purpose is to analysis the performance of the circuit whether the circuit having a good condition or not based on the performance at cornering section. This target can be achieved by doing the simulation with current software. For this project, the software that being used is CarMaker software. The needed for this simulation are only the circuit and the model of the vehicle. For the circuit, the dimension and shape is taken by doing some estimation from the real circuit. The dimension can be changes since the circuit actually used for the go-cart race. But the important is the shape must follow with the actual one. For this project, the car model that being used is Perodua Kancil EX660. All the specifications and dimensions of the car can be added in the software to generate the new small car for the simulation. A modified technique of by the CarMaker software is proposed and critically analyzed. This analysis indicated that a methodical approach to vehicle set up and optimization combined with lap time simulation can give the best result to find the forces acting on the car and study about cornering. Not only for the car, had the project also studied about the performance of the circuit while the car is moving on it. To study about performance of the circuit, the preliminary result must be obtained in this project. By getting all the information, we can conclude that whether the circuit has a good performance or not especially on the cornering.